Ruqyah Syar'iyyah as an Alternative to Non-Litigation Mediation in Domestic Conflicts - M. Fatkhul Alim; Burhanatut Dyana; Indah Listyorini (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
Mediators in court are often constrained by formal rules, limiting their ability to explore the root causes of conflict in depth. This situation causes mediation in court to tend to fail to achieve peace. The purpose of this study is to describe and analyze Ruqyah Syar'iyyah as an effort to resolve family conflicts. This study uses qualitative research with a case study approach. Ruqyah is perceived as a more humane, non-confrontational method that is more in line with the cultural values of the local Muslim community. research shows that in Bojonegoro there is Qur'anic Healing Indonesia (QHI), a ruqyah institution that handles various issues, not only spiritual matters but also family conflicts, opening opportunities for religious institutions, religious counselors, and family mediators to develop a mediation model that combines a spiritual and communicative approach that is humane, contextual, and capable of strengthening the emotional relationship between couples. This limitation shows the need for alternative approaches outside the formal litigation system, giving rise to non-litigation mediation as an approach that is considered more flexible and responsive in resolving family conflicts. Ruqyah Syar'iyyah is seen as capable of providing peace of mind and opening the religious awareness of couples in conflict. This method of ruqyah syar'iyyah (QHI) has the disadvantage of being rarely successful in cases of polygamy, but it has the advantage of being successful in cases of quarrels.